Pemanfaatan Jurnal Ilmiah untuk Meningkatkan Kemampuan Literasi Sains, Hasil Belajar dan Motivasi Belajar Peserta Didik - Azizah Rahmy; Annisaul Khairat (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Scientific literacy is very important in the 21st century era so that students have life skills in dealing with advances in science and technology. This study aims to (1) look at students' scientific literacy abilities by utilizing scientific journals as research-based learning materials (2) find out students' learning outcomes and (3) find out students' learning motivation. This research is a best practice from the authors whose data is in the form of quantitative descriptive data. This research is based on data obtained from observations during the learning process, the results of students' pretest and posttest after participating in learning by carrying out data calculations using simple statistical data. This research was conducted in class VII. 1 MTsN 1 Tanah Datar which consists of 25 students. The data collection technique used is the result of an assessment of scientific literacy abilities and an assessment of student learning outcomes. Students take two types of tests, namely in the form of tests with literacy questions that refer to AKMI, ANBK questions and PISA questions related to environmental quality. The results showed that the average classical score of students' scientific literacy skills from three meetings was 42.67 with a proficiency level classified as proficient. Proficient means that students are able to identify and distinguish scientific questions about procedural knowledge in personal and local-national contexts. While the assessment of student learning outcomes averaged 88.60, where out of 25 students, 24 students achieved grades above the KKM.